حكم زكاة مال الصبي عند المذاهب الأربعة: The Law of Zakat on the Assets of a Child According to the Views of the Four Schools - Rosmita Rosmita; Mukran H. Usman; Riska Riska; Karmila Karmila (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the law of zakat on the assets of young children according to the four schools of thought and to analyze the opinions of scholars of the four schools regarding the law of zakat on the assets of young children. The research method used is inductive and comparative methods. The results of this study are: first, according to Hanafi, the law of zakat on the assets of young children is not obligatory, while according to the Maliki, Shafi'i and Hambali schools, it is obligatory. Hanafi is of the opinion that zakat is worship that is mahḍah which requires the age of maturity and intelligence, while the Maliki, Shafi'i and Hanbali schools do not require adulthood and have reason in it, because of the generality of the zakat verses and the existing hadiths, so they view that it is obligatory; second, based on the results of the analysis, the researcher believes that zakat on the assets of young children must be paid zakat for several reasons other than the arguments of the Al-Qur'an and Sunnah, including zakat is a property worship, and small children may own these assets, so that the right of the indigent The poor should not be prohibited from receiving zakat assets.